Marine environmental education at Seaworld, Durban: A review and update - Trevlyn Renald (Environmental Association of Southern Africa, 1988)
The South African Association for Harine Biological Research (SAAHBR), established in 1957, has played an important role primarily in coastal research, through the Oceanographic Research Institute (ORI) and as a public education centre through Seaworld, comprising the aquarium and dolphinarium. During the last twelve years education facilities have been developed for school groups, and in particular for the senior primary level. These facilities include volunteer guides, tours, educational material and field courses. More recently the emphasis has moved to include resources for the secondary school level, part of an attempt to broaden the base of the user group.